Intervensi penatalaksanaan gizi dalam meningkatkan kadar hemoglobin dan tumbuh kembang balita stunting - Delima Citra Dewi Gunawan; Endri Yuliati (Jurnal Gizi Klinik Indonesia, 2019)
The intervention of nutrition management can increase hemoglobin levels and development on stunting toddlerBackground: The prevalence of stunting remains high in Indonesia. Stunting has serious effects on children such as increased morbidity, mortality, and decreasing physical and cognitive capability. Objectives: To analyze the effect of the nutrition care process on nutritional status, hemoglobin, and development on stunting children. Methods: This quasi-experimental study used a non-randomized pre and post-test with a control group design. Fortyfour children under five were divided into 2 groups; the intervention group received the nutrition care process for 3 months, while a control group received a leaflet. Nutritional status was determined by body weight for age, hemoglobin concentration using finger test stick, and development using a questionnaire. Results: There were significant differences (p<0.05) in weight for age between the two groups, both before and after the intervention. However, the differences of weight for an age before and after intervention in each group were not significant (p=0.184 and p=0.130). The increase of hemoglobin concentration between before and after intervention in the intervention group was statistically significant (p=0.008). On the other hand, there was a significant decrease in hemoglobin concentration in a control group (p=0.003). There was an increase of subjects having accordance development, from 9 to 15 subjects in the intervention group. The development between before and after the intervention was significantly different (p=0.03), but not in the control group (p=0.78). Conclusions: The nutrition care process could accelerate the improvement of hemoglobin concentration and development, but not on the nutritional status of stunting children.